FAERS based disproportionality analysis and network pharmacology investigation of taxanes associated drug induced liver injury - Cheng, Yijie; Yang, Yuxin; Su, Yan; Chen, Ruihuan; Qian, Da; Xu, Jingyuan (Scientific reports, 2025)
Taxanes play a crucial role in cancer treatment, particularly for non-small cell lung cancer and breast cancer. However, real-world studies examining drug-induced liver injury (DILI) associated with these drugs remain limited. Our study investigates the association between taxanes and DILI through analysis of the Food and Drug Administration Adverse Event Reporting System (FAERS) database, alongside an exploration of potential hepatotoxicity mechanisms via network pharmacology. We collected DILI reports related to taxanes from the FAERS database between January 2004 and March 2024, employing disproportionality analyses with the reporting odds ratio (ROR) and 95% confidence intervals. Our findings revealed a significant association between paclitaxel (ROR = 2.35) and nab-paclitaxel (ROR = 3.14) with DILI, while docetaxel demonstrated no significant correlation (ROR = 0.68), although it was linked to higher mortality rates and earlier onset. Network pharmacology analysis uncovered that the mechanisms of liver injury induced by these two drugs may not be entirely congruent. Unique targets for docetaxel included BCL2, CNR2, and MAPK1, while the ‘Regulation of lipolysis in adipocytes’ pathway was specifically associated with docetaxel-induced DILI. Our findings indicate that taxanes exhibit differential hepatotoxic risks and hepatotoxicity mechanisms, emphasizing the need for enhanced drug safety monitoring strategies for cancer patients.